Vitamin D enhances the efficacy of photodynamic therapy in a murine model of breast cancer. (25th February 2015) - Rollakanti, Kishore R.; Anand, Sanjay; Maytin, Edward V.
Abstract Cutaneous metastasis occurs more frequently in breast cancer than in any other malignancy in women, causing significant morbidity. Photodynamic therapy (PDT), which combines a porphyrin‐based photosensitizer and activation by light, can be employed for breast cancer (especially cutaneous metastases) but tumor control after PDT has not surpassed traditional treatments methods such as surgery, radiation, and chemotherapy up to now. Here, we report that breast cancer nodules in mice can be effectively treated by preconditioning the tumors with 1α, 25‐dihydroxyvitamin D3 (calcitriol; Vit D) prior to administering 5‐aminolevulinate (ALA)‐based PDT. Breast carcinoma tumors (MDA‐MB‐231 cells implanted subcutaneously in nude mice) received systemic Vit D (1 μg/kg) for 3 days prior to receiving ALA. The addition of Vit D increased intratumoral accumulation of protoporphyrin IX (PpIX) by 3.3 ± 0.5‐fold, relative to mice receiving ALA alone. Bioluminescence imaging in vivo and immunohistochemical staining confirmed that tumor‐specific cell death after ALA‐PDT was markedly enhanced (36.8 ± 7.4‐fold increase in TUNEL‐positive nuclei; radiance decreased to 14% of control) in Vit D pretreated tumors as compared to vehicle‐pretreated tumors. Vit D stimulated proliferation (10.7 ± 2.8‐fold) and differentiation (9.62 ± 1.7‐fold) in tumor cells, underlying an augmented cellular sensitivity to ALA‐PDT. The observed enhancement of tumor responses to ALA‐PDT after low, nontoxic doses of Vit D supports a new combination approach that deserves consideration in the clinical setting, and offers potential for improved remission of cutaneous breast cancer metastases.